Village Fund Management Accountability in Disadvantaged Village Cluster - Sufi, Rifai (Publication Division of International Ecsis Association, 2022)
This study aims to analyze how the implementation of village fund management and the concept of Village Fund Management Accountability in the underdeveloped Village Cluster in Bobane Indah Village, West Patani District, Central Halmahera Regency. The method in this research is qualitative. Data collection was carried out using in-depth interview methods. Village observations and documents such as APBDes and Budget Realization Reports for 2019 and 2020. The number of informants in this research is 5 (five) informants who are village officials. The results of the study indicate that the Accountability of Village Fund management in Bobane Indah Village has met the procedures and compliance in administrative village financial management has met the requirements that apply normatively and assessment with indicators of compliance with procedures, indicators of expectations, and targets of officers, indicators of conformity between targets and program achievements, indicators of budget transparency and financial accountability, indicators of social interaction regarding the management of Village Funds in Bobane Indah Village have been realized.